Cover Image. Issue 3 (23rd January 2018) - Costa, Pedro M.; Gosens, Ilse; Williams, Andrew; Farcal, Lucian; Pantano, Daniele; Brown, David M.; Stone, Vicki; Cassee, Flemming R.; Halappanavar, Sabina; Fadeel, Bengt
Abstract : The cover image, by Pedro M. Costa et al., is based on the research Article Transcriptional profiling reveals gene expression changes associated with inflammation and cell proliferation following short‐term inhalation exposure to copper oxide nanoparticles, DOI:10.1002/jat.3548